On-Going Morphosyntax Supplementary Material - Caltira Rosiana (STKIP PGRI Nganjuk, 2018)
Studying morphosyntax is important in the study of linguistics and the topic of morphosyntax is very often considered as difficult to learn. However, several problems still occur in almost every linguistics class including problems from the students’ characteristics, learning materials, teaching strategies, etc. Therefore, the researchers conducted a preliminary study in a linguistic class. Based on the preliminary study, it was discovered that most of the students involved in the study lacked motivation to study linguistic especially in studying morphosyntax and lacked sources to study morphosyntax. The lecturer also had some difficulties in providing morphosyntax material which could motivate the students to learn morphosyntax with ease and which was suitable for the curriculum standards well as the students’ need. Because of those problems, this research aimed to develop supplementary morphosyntax materials for university students which could help them to cope with their problems in studying morphosyntax through providing the easy-to-understand supplementary material which accommodated the students’ needs. It is expected that this research can inspire the lecturers who teach linguistics to become more creative and innovative in providing materials which match the students’ need and syllabus. However, this supplementary material is only one of the alternatives that can be used to assist the learning process. Thus, it can also be combined with other resources. To achieve the aim of this study, the researcher used research and development design by following Borg and Gall model. The researcher did the preliminary study, designed the problem solving and developed the supplementary material since at the end of November 2016. The researcher also conducted expert validations for the product, revised the product draft, applied the product, revised the product again, conducted the second product implementation, had another product validation, and finally had the final product in the form of morphosyntax module.